Cabaran guru dalam pengajaran digital secara maya dan kesediaan murid pasca Covid-19 [Teacher challenges in online teaching and student readiness post Covid-19} - Nik Abdullah, Nik Md. Saiful Azizi; Ali, Rohani; Yahya, Nurul Nadiah; Muhammad Isa, Rabi'atul Athirah (Centre for Core Studies, Universiti Sains Islam Malaysia, 2021)
Covid-19 is a new virus that began to become a pandemic in early 2020 and has had a major impact on the teaching and learning process. Thus, the objective of this study was to identify the challenges that teachers face when dealing with the Covid-19 pandemic while conducting teaching sessions with students, as well as to investigate students' readiness during new norm teaching and learning. This study was conducted using qualitative methods through interviews involving 10 school students and document analysis. The findings of the study indicate the challenges faced by teachers such as the implementation of online teaching and lack of readiness of digital infrastructure. In addition, the challenges of implementing face-to-face learning and blended learning. Meanwhile, the challenges of student readiness such as lack of attention from parents who work as frontliners during movement control orders (PKP), the convenience of smartphone, computer devices and internet access facilities. The implications are the need to re-evaluate educational objectives and change towards beyond examinations by the Malaysian ministry of education, distribute devices and increase access to online classes, expand access to students through television and expand digital access to all communities whether urban or rural.